Association of 3-Phenoxybenzoic Acid Exposure during Pregnancy with Maternal Outcomes and Newborn Anthropometric Measures - Guimarães, Juliana (2023)
Funding Information: The authors would like to thank the kind participation of all pregnant women and the support of the recruitment activities by the health professionals of the Department of Obstetrics, Centro Hospitalar Universitário S. João, Porto, Portugal and also to the professionals of REQUIMTE/LAQV, Instituto Superior de Engenharia, Politécnico do Porto, for their collaboration in carrying out the analyzes of the 3-PBA metabolite. This work received support from PT national funds (FCT/MCTES, Fundação para a Ciência e Tecnologia and Ministério da Ciência, Tecnologia e Ensino Superior) through the projects LA/P/0053/2020; UIDB/4255/2020; UIDB/5006/2020 and UIDP/50006/2020. Virgínia Cruz Fernandes thanks FCT/MCTES (Fundação para a Ciência e Tecnologia and Ministério da Ciência, Tecnologia e Ensino Superior) and ESF (European Social Fund) through NORTE 2020 (Programa Operacional Região Norte) for his/her Post-Doc grant ref. SFRH/BPD/109153/2015). Juliana Guimarães was funded by FCT/MCTES (Foundation for Science and Technology and Ministry of Science, Technology and Higher Education) under CINTESIS by a PhD scholarship (reference UI/BD/152087/2021). Funding Information: This article was supported by national funds through the FCT Foundation for Science and Technology, I.P., within the scope of the projects RISE - LA/P/0053/2020; CINTESIS, R&D UNIT (reference UIDB/4255/2020) and LAQV (references: UIDB/50006/2020 AND UIDP/50006/2020). Virgínia Cruz Fernandes was funded by FCT/MCTES (Foundation for Science and Technology and Ministry of Science, Technology and Higher Education) and the ESF (European Social Fund) through NORTE 2020 (North Region Operational Program) through a grant of Post-Doc (reference SFRH/BPD/109153/2015). Juliana Guimarães was funded by FCT/MCTES (Foundation for Science and Technology and Ministry of Science, Technology and Higher Education) under CINTESIS by a PhD scholarship (reference UI/BD/152087/2021). Publisher Copyright: © 2023 by the authors.